Equilibrium, Kinetic, and Thermodynamic Studies on the Adsorption of Cadmium from Aqueous Solution by Modified Biomass Ash - Lei Xu; Xuebo Zheng; Hongbiao Cui; Zhenqiu Zhu; Jiani Liang; Jing Zhou (Bioinorganic Chemistry and Applications)
Natural biomass ash of agricultural residuals was collected from a power plant and modified with hexagonal mesoporous silica and functionalized with 3-aminopropyltriethoxysilane. The physicochemical and morphological properties of the biomass ash were analyzed by ICP-OES, SEM, TEM-EDS, FTIR, and BET analysis. The adsorption behavior of the modified product for Cd2+ in aqueous solution was studied as a function of pH, initial metal concentration, equilibrium time, and temperature. Results showed that the specific surface area of the modified product was 9 times that of the natural biomass ash. The modified biomass ash exhibited high affinity for Cd2+ and its adsorption capacity increased sharply with increasing pH from 4.0 to 6.0. The maximum adsorption capacity was 23.95 mg/g in a pH 5 solution with an initial metal concentration of 50 mg/L and a contact time of 90 min. The adsorption of Cd2+ onto the modified biomass ash was well fitted to the Langmuir model and it followed pseudo-second-order kinetics. Thermodynamic analysis results showed that the adsorption of Cd2+ was spontaneous and endothermic in nature. The results suggest that the modified biomass ash is promising for use as an inexpensive and effective adsorbent for Cd2+ removal from aqueous solution.